Analysis of Energy Losses in Medium Voltage Distribution Conductors Based on Load Curve: A Case Study on the Sindanglaut Feeder - Marriwanto, Pirdo; Tobaristan, Haris; Taryo, Taryo (PT FORMOSA CENDEKIA GLOBAL, 2025)
Power losses in electrical distribution systems are a major challenge that can reduce the efficiency of energy delivery. This study focuses on reducing such losses in medium-voltage distribution networks, particularly on the Sindanglaut Feeder at the Ciledug customer service unit of the State Electricity Company. The analysis employed load flow simulations using ETAP 12.6.0 software, with an optimization strategy of increasing the cable cross-section from 150 mm² to 240 mm² to assess its impact on voltage drop and distribution efficiency. Simulation results indicated that, prior to optimization, the average active power was 1.40 kW, reactive power was 5.75 kVar, and voltage drop was 3.28%. After optimization, these values decreased to 1.13 kW, 5.16 kVar, and 2.76%, accompanied by a significant reduction in total power losses. These findings demonstrate that cable size adjustment based on technical analysis is effective in improving distribution system performance and can serve as a reference for developing efficient, data-driven distribution networks.